Physiochemical composition and antioxidant activities of underutilized Mangifera pajang fruit - Ibrahim, Muhammad; Prasad, K. Nagendra; Ismail, Amin; Azlan, Azrina; Abdul Hamid, Azizah (Academic Journals, 2010)
Underutilized plant species are defined by their unexploited economic potential, making them an appropriate focus for commercialization. The physiochemical composition and antioxidant activities of underutilized Mangifera pajang Kosterm fruit pulp and fruit juice powder were studied. The average kernel weight and length of M. pajang fruits was higher compared to Mangifera india. Chemical composition revealed that M. pajang juice powder (MPJP) was high in protein, carbohydrate, ascorbic acid, and ash whereas M. pajang pulp (MPP) was rich in fiber, gross energy, phenolic and β-carotene content. Additionally, MPJP extract exhibited the highest free radical scavenging activities by 1,1-diphenyl-2-picrylhydrazyl (DPPH)and ferric reducing antioxidant power (FRAP) methods. The antioxidant capacity of MPP and MPJP extracts were significantly correlated with the ascorbic acid and β-carotene but not with phenolic content. The high antioxidant activity with high ascorbic acid, proteins and carbohydrate content suggested that the MPJP can be used as a good source for preparation of health drink.